Fatal Myelotoxicity Following Palliative Chemotherapy With Cisplatin and Gemcitabine in a Patient With Stage IV Cholangiocarcinoma Linked to Post Mortem Diagnosis of Fanconi Anemia - Engel, Nils W.; Schliffke, Simon; Schüller, Ulrich; Frenzel, Christian; Bokemeyer, Carsten; Kubisch, Christian; Lessel, Davor (Frontiers in Oncology, 2019)
Unrecognized genome instability syndromes can potentially impede the rational treatment of cancer in rare patients. Identification of cancer patients with a hereditary condition is a compelling necessity for oncologists, giving varying hypersensitivities to various chemotherapeutic agents or radiation, depending on the underlying genetic cause. Omission of genetic testing in the setting of an overlooked hereditary syndrome may lead to unexpected and unbearable toxicity from oncological standard approaches. We present a case of a 33-year-old man with an early-onset stage IV intrahepatic cholangiocarcinoma, who experienced unusual bone marrow failure and neutropenic fever syndrome as a consequence of palliative chemotherapy containing cisplatin and gemcitabine, leading to a fatal outcome on day 25 of his first chemotherapeutic cycle. The constellation of bone marrow failure after exposure to the platinum-based agent cisplatin, the presence of an early-onset solid malignancy and the critical appraisal of further phenotypical features raised suspicion of a hereditary genome instability syndrome. Whole-exome sequencing from buccal swab DNA enabled the post mortem diagnosis of Fanconi anemia, most likely linked to the fatal outcome due to utilization of the DNA crosslinking agent cisplatin. The patient´s phenotype was exceptional, as he never displayed significant hematologic abnormalities, which is the hallmark of Fanconi anemia. As such, this case stresses the importance to at least question the possibility of a hereditary basis in cases of relatively early-onset malignancy before defining an oncological treatment strategy.